ADAPTASI HARGA JUAL KERIPIK KENTANG TERHADAP FLUKTUASI HARGA BAHAN PRODUKSI PADA HOME INDUSTRY UD. KERIPIK KENTANG ANIS - AGRIZKY SATIVA CAHYANI; EJA ARMAZ HARDI; G.W.I. AWAL HABIBAH (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The need for basic materials is an important thing that humans need to fulfill their daily needs. This need increases every year, the economic challenge that arises is the increase in prices, especially the price of basic materials. From this price determination, price problems often occur, one of which is a problem that is very vulnerable to price fluctuations. , from the fluctuating prices of basic commodities which have an impact on society, the increase in prices of basic commodities certainly affects the operational costs of both individual households and has an impact on a business, one of which is the home industry business. The aim of this thesis is:1. To find out what adaptation strategies are used to deal with fluctuations in the price of production materials at UD. Anis potato chips 2. To find out how prices are determined when prices of production materials fluctuate. This thesis uses a qualitative approach, the informants in this research are home industry owners and home industry customers, using data collection methods through observation, interviews and documentation. The research results show:1. Adaptation strategies carried out to maintain business in the UD home industry. Anis’s potato chips include creative change (making changes), customer focus (customer focus), and organizational learning (organizational learning).2. Determining prices when prices fluctuate, namely by paying attention to price affordability, price suitability to product quality, and price suitability to product benefits.It is hoped that the results of this research will be useful for increasing knowledge and insight in how to adapt or survive in the face of fluctuations in the price of production materials.